1999
DOI: 10.1038/sj.onc.1202415
|View full text |Cite
|
Sign up to set email alerts
|

Detailed methylation analysis of the glutathione S-transferase π (GSTP1) gene in prostate cancer

Abstract: Glutathione-S-Transferases (GSTs) comprise a family of isoenzymes that provide protection to mammalian cells against electrophilic metabolites of carcinogens and reactive oxygen species. Previous studies have shown that the CpG-rich promoter region of the p-class gene GSTP1 is methylated at single restriction sites in the majority of prostate cancers. In order to understand the nature of abnormal methylation of the GSTP1 gene in prostate cancer we undertook a detailed analysis of methylation at 131 CpG sites s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(141 citation statements)
references
References 31 publications
2
138
1
Order By: Relevance
“…The GSTP1 variant genotype was seen in increased numbers of tumors of the kidney, bladder, pancreas and lung (To-Figueras et al, 1999;Simic et al, 2009;Vrana et al, 2009). GSTP1 has a polymorphic site at codon 105 (exon 5), where an A to G transition causes an Ile to Val substitution (Ile105Val), resulting in lower enzyme activity to variety of electrophilic molecules (Millar et al, 1999;Hayes et al, 2005;McIlwain et al, 2006). Numerous reports assessed the risk of colorectal cancer development in subjects carrying the variant Val GSTP1 allele; however, the results are controversial (Harries et al, 1997;Welfare et al, 1999;Kiyohara, 2000;Grubben et al, 2001;Loktionov et al, 2001;Seow et al, 2002;Ates et al, 2005;Sun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The GSTP1 variant genotype was seen in increased numbers of tumors of the kidney, bladder, pancreas and lung (To-Figueras et al, 1999;Simic et al, 2009;Vrana et al, 2009). GSTP1 has a polymorphic site at codon 105 (exon 5), where an A to G transition causes an Ile to Val substitution (Ile105Val), resulting in lower enzyme activity to variety of electrophilic molecules (Millar et al, 1999;Hayes et al, 2005;McIlwain et al, 2006). Numerous reports assessed the risk of colorectal cancer development in subjects carrying the variant Val GSTP1 allele; however, the results are controversial (Harries et al, 1997;Welfare et al, 1999;Kiyohara, 2000;Grubben et al, 2001;Loktionov et al, 2001;Seow et al, 2002;Ates et al, 2005;Sun et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of the GSTP1 CpG island is an early and common event in prostate cancer (Brooks et al, 1998;Cookson et al, 1997;Esteller, 2000;Lee et al, 1994;Millar et al, 1999;Moskaluk et al, 1997). We previously reported that the methylation pattern across the GSTP1 CpG island in the prostate cancer cell line LNCaP is extensive and the gene is silent (Millar et al, 1999(Millar et al, , 2000.…”
Section: Gstp1 Methylation In Lncap and Du145 Cell Linesmentioning
confidence: 99%
“…We previously reported that the methylation pattern across the GSTP1 CpG island in the prostate cancer cell line LNCaP is extensive and the gene is silent (Millar et al, 1999(Millar et al, , 2000. Essentially all the CpG sites are methylated extending past the ATAAA repeat motif through the promoter region and into the body of the gene (Figure 2).…”
Section: Gstp1 Methylation In Lncap and Du145 Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations